Estudio sobre competitividad de las empresas comercializadoras de té, en Morelia, México y Nueva York, Estados Unidos - Macouzet Ramírez, Mariana (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
This research project describes the tea salon industry, and proposes a study to understand the conditions of this sector in Mexico and in the United States, particularly in Morelia and New York. The main objective of the research is to understand how quality, innovation, marketing and finances have influenced the competitiveness of businesses dealing with this beverage, in both cities. After describing the problem observed, the relevance of a study of competitiveness in the sector is justified. Also, a theoretical framework that enables a study of the performance of businesses and a comparative analysis between cities is suggested. The proposition of this project is a quantitative study of scientific character. Methodology concerns the application of a questionnaire designed to obtain and interpret statistical data leading to conclusions and recommendations regarding competitiveness of tea salons in both Morelia and New York. The theoretical perspective that sustains this master‘s degree dissertation, is built upon four theories of competitiveness, and some of their contributions to economics: the competitive advantage, the resource based view, the evolutionary economic theory and the systemic competitiveness. This research concludes that the total competitiveness for tea salons both in Morelia and New York vary between 97 points, or regular competitiveness, and 143 points, or very high competitiveness. All these companies are regularly competitive, highly competitive or very highly competitive. None of the tearooms showed low or very low competitiveness.

El presente proyecto de investigación aborda la problemática existente en la industria de la comercialización del té, y plantea un estudio que analice las condiciones en las cuales se encuentra dicho sector en México y en Estados Unidos, más específicamente en las ciudades de Morelia y Nueva York. El objetivo de la investigación es conocer de qué manera han influido la calidad, la innovación, la mercadotecnia y las finanzas, en la competitividad de las empresas dedicadas a la comercialización de este tipo de bebidas, en ambas ciudades. Tras plantear la problemática, se justifica la relevancia de realizar un estudio sobre la competitividad en el sector, y se aborda un marco teórico que posibilita el estudio del desempeño de las empresas y un análisis comparativo entre ciudades. La propuesta que se plantea en este proyecto es un estudio cuantitativo de carácter científico, mediante la aplicación de cuestionarios diseñados para obtener e interpretar datos estadísticos que permitan asimismo formular conclusiones y recomendaciones sobre la competitividad de las empresas comercializadoras de té, de Morelia y Nueva York. La perspectiva teórica sobre la cual estará sustentada esta tesis maestral, se construye a partir de cuatro teorías sobre competitividad, y algunos de sus aportes a la economía: la ventaja competitiva, la perspectiva basada en los recursos, la teoría evolutiva y la competitividad sistémica. Se concluyó que la competitividad total de las empresas morelianas y neoyorquinas varía entre los 97 puntos, regular competitividad, y los 143 puntos, muy alta competitividad. Todos los salones de té entrevistados en Morelia y en Nueva York son regularmente competitivos, altamente competitivos o muy altamente competitivos. Ninguna casa de té tiene baja o muy baja competitividad.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Negocios Internacionales
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2017-0776; Calidad; Innovación; Mercadotecnia; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1050